The Effect of Air-Water-Plasma-Jet-Activated Water on Penicillium: The Reaction of HNO2 and H2O2 Under Acidic Condition - Liu, Kun; Liu, Shi-ting; Ran, Cong-fu (Frontiers in Physics, 2020)
Plasma-activated water (PAW) is produced by microhollow cathode discharge (MHCD), where air is the working gas used. The treatment effect of PAW against Penicillium is expressed by the germination inhibition rate and the sporoderm-breakage rate. The maximum values of the germination inhibition rate and the sporoderm-breakage rate are 82.31 and 66.91%, respectively. In this paper, the importance of the reaction of HNO2 and H2O2 in Penicillium inactivation is illustrated, which is most likely due to its product—ONOOH. The effective impact of ONOOH on inactivation beyond its theoretical lifetime is indirectly reflected by the treatment efficiency, and the complexity of peroxynitrite chemistry may be responsible for prolonging this effect. Moreover, according to the difference of concentration magnitude between HNO2 and H2O2, and the reaction of them under acidic conditions, a method to increase the H2O2 production is demonstrated, which can contribute to improving the yield of ONOOH.